2007
DOI: 10.20867/thm.13.3.18
|View full text |Cite
|
Sign up to set email alerts
|

The Logistics of Selling a Destination’s Tourism Product∗

Abstract: Tourism demand is becoming increasingly more discerning. It expects a well-designed and diverse product. This can be achieved with properly organised receiving-tourism facilities and services, and an array of attractions and entertainment events. Parallel to enhancing attractiveness, it is also necessary to strengthen and intensify internal and external marketing to ensure that a destination product and, in particular, its segments will find customers on the market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, tourist attractions, events, local food and craft products can provide an excellent opportunity to experience the local culture (Lončarić et al 2021), sensitising visitors to explore the various aspects that characterise a place. Finally, from an economic and market point of view, the range and quality of services greatly influence the success of a tourist destination (Radisic and Basan 2007). However, the results also demonstrated that visitors are generally inclined to set lower priorities for strategies related to retail and souvenir shops than those assigned to other management issues.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, tourist attractions, events, local food and craft products can provide an excellent opportunity to experience the local culture (Lončarić et al 2021), sensitising visitors to explore the various aspects that characterise a place. Finally, from an economic and market point of view, the range and quality of services greatly influence the success of a tourist destination (Radisic and Basan 2007). However, the results also demonstrated that visitors are generally inclined to set lower priorities for strategies related to retail and souvenir shops than those assigned to other management issues.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the Visitor use management system, tourists confirmed the need to intervene with almost the same level of medium-high priority already established in the current Management Plan. As stated in other studies (Radisic andBasan 2007, Lončarić et al 2021), it is fundamental for managers of nature-based destinations to disseminate information on the various natural attractions and services available, using communications materials, web pages and social media. By being informed in advance, visitors would be facilitated in planning their trip, which would increase their satisfaction with the chosen destination.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations